Injury recognition and prevention : lower and upper extremity - Ludwig, Genevieve (Momentum Press, 2016)
This book covers the most common musculoskeletal injuries of the arms, legs, and spine. The text is designed to be a reference tool for students and professionals who work with athletes or a physically active population. Each chapter covers a specific anatomical joint area and includes a brief review of musculoskeletal anatomy, common injury etiology, signs and symptoms for easy recognition, and the most commonly prescribed treatment or rehabilitation plan. Also discussed are preventative measures to avoid sustaining these common injuries. Coaches, students in allied health professions, physical education teachers, parents, and athletes will benefit from reading this text. The first part of the text discusses lower extremity injuries, including commonly seen issues of the foot, ankle, lower leg, knee, hip, and lumbar spine. The second part of the text discusses upper extremity injuries, including commonly seen issues of the shoulder, elbow, wrist and hand, cervical spine, and head injuries.